2014
DOI: 10.1021/jp502420x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Description of Surfactant-like Peptide Based Membranes

Abstract: For first time surfactant-like peptide (SLP) based membranes were investigated by full atomistic molecular dynamics simulations. Two different classes of membranes were simulated to quantify the impact of both nonpolar tail and hydrophilic head on the membrane properties. Structural analysis in terms of planar RDFs, density mass profiles, and 2D thickness maps was performed to evaluate the influence of the hydrophobic tail and hydrophilic head in the membrane structural pattern. Unlike what is observed in case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…50 It was for the first time that the RCs were used in an electrolyte-less energy device when Rupa das et al reported the photoelectric performance of an RC immobilized solid state set up (Fig 4(d)). 26 Surfactant like peptides [111][112][113][114] have been used to stabilize the RC complexes and a subnanometer thick layer of 55 amorphous organic semiconductor has been deposited in between the RC and the metal electrode to serve as a solid state antenna enhancing the light absorption. 26 Rupa das et al constructed an RC based solid state electronic device with a conductive ITO coated glass electrode, coated further by a nanolayer of gold 60 anode (with a Cr adhesion layer in between Au and ITO) to which MHisRCs are oriented by an Ni-NTA SAM on the gold surface.…”
Section: Rcs Bound To Nanotubesmentioning
confidence: 99%
“…50 It was for the first time that the RCs were used in an electrolyte-less energy device when Rupa das et al reported the photoelectric performance of an RC immobilized solid state set up (Fig 4(d)). 26 Surfactant like peptides [111][112][113][114] have been used to stabilize the RC complexes and a subnanometer thick layer of 55 amorphous organic semiconductor has been deposited in between the RC and the metal electrode to serve as a solid state antenna enhancing the light absorption. 26 Rupa das et al constructed an RC based solid state electronic device with a conductive ITO coated glass electrode, coated further by a nanolayer of gold 60 anode (with a Cr adhesion layer in between Au and ITO) to which MHisRCs are oriented by an Ni-NTA SAM on the gold surface.…”
Section: Rcs Bound To Nanotubesmentioning
confidence: 99%
“…Unlike conventional surfactants whose hydrophobic tails interact in all directions through hydrophobic interactions, the amphiphilic peptide tail contains not only hydrophobic groups but also hydrophilic sites. 14,15 This feature allows the SLPs to stabilize nanostructures in one direction through hydrophobic interactions and in the orthogonal direction by hydrogen bonds. 14,15 Hydrogen bonds associated with hydrophobic interactions can stabilize even more complex secondary structures such as helices and sheets, whereas conventional lipids/surfactants are basically organized into micelles, vesicles and nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 This feature allows the SLPs to stabilize nanostructures in one direction through hydrophobic interactions and in the orthogonal direction by hydrogen bonds. 14,15 Hydrogen bonds associated with hydrophobic interactions can stabilize even more complex secondary structures such as helices and sheets, whereas conventional lipids/surfactants are basically organized into micelles, vesicles and nanotubes. 14,15 In addition to the remarkable characteristics related to self-assembly, amphiphilic peptides also have desirable antibacterial properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical chemical properties of self-assembling systems [1][2][3] and bilayers [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] constitute a large body of biophysical research. Computer simulation, in particular molecular dynamics (MD), provides an important contribution to these investigations as an atomistic-precision tool.…”
Section: Introductionmentioning
confidence: 99%